The Effect of Rekattidiri Ovitrap towards Aedes aegypti Larval Density - Malik Saepudin; Soeharyo Hadisaputro; Ari Suwondo; Suhartono Suhartono (International Journal of Public Health Science (IJPHS), 2017)
Dengue Hemorrhagic Fever (DHF) is a health problem in Indonesia. The entire region of Indonesia at risk of contracting dengue disease. The study aims to prove the effect of modifications ovitrap rekattidiri on the density of larvae (HI: House Index, CI: Container Index and BI: Breteu Index) as well as comparing the differences between the mean larvae trapped between ovitrap Rekattidiri with standard ovitrap. Using a quasi experimental design, time series experimental design with Control group. Population subjects were Aedes aegypti at the endemic sites in Pontianak, West Borneo. The results showed larval density index in the intervention area decreased each ie HI from 26% to 3%, CI of 6.95% to 2.19 %, and BI from 29% to 13%. The number of larvae trapped in ovitrap rekattidiri ie 70% (12,770 larvae) more than the standard ovitrap in the control and intervention, namely: 17% (3,057 larvae) and 13% (2,334 larvae). It is concluded that there are significant modifications Rekattidiri ovitrap against larval density index (HI p-value: 0.025, CI p-value: 0.052, BI value of p: 0.04) and there are differences between the mean larvae trapped in ovitrap Rekattidiri and standard ovitrap with p value: 0.001.